2017
DOI: 10.2147/dddt.s126861
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tolerability of DA-8031, a novel selective serotonin reuptake inhibitor for premature ejaculation in healthy male subjects

Abstract: ObjectiveDA-8031 is a selective serotonin reuptake inhibitor under development for the treatment of premature ejaculation. This is the first-in-human study aimed at evaluating the pharmacokinetics and tolerability of DA-8031 and its metabolites (M1, M2, M4, and M5) in the plasma and urine after administration of a single oral dose in healthy male subjects.MethodsA dose block-randomized, double-blind, placebo-controlled, single ascending dose study was conducted. Subjects received either placebo or a single dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The commonest adverse events were nausea and hypotension. The authors found that a dose of 120 mg was associated with prolongation of the QT interval on electrocardiogram 88 . This is potentially a very exciting drug for the future, and further studies are awaited ( Table 5 ).…”
Section: Management Options: Novel Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The commonest adverse events were nausea and hypotension. The authors found that a dose of 120 mg was associated with prolongation of the QT interval on electrocardiogram 88 . This is potentially a very exciting drug for the future, and further studies are awaited ( Table 5 ).…”
Section: Management Options: Novel Agentsmentioning
confidence: 99%
“…In addition, it is associated with reduced serotonin transporter occupancy, confirmed on positron emission tomography of the rat brain 87 . This was recently evaluated in the first human trial to assess safety and tolerability after a single dose in healthy men 88 . Men were randomly assigned to receive either the active drug or placebo.…”
Section: Management Options: Novel Agentsmentioning
confidence: 99%
“…DA-8031 is a novel SSRI for the treatment of PE. 15 , 16 In a preclinical study in rats, DA-8031 delayed the latency to ejaculation. 15 In a first-in-human single ascending dose clinical study, DA-8031 was rapidly absorbed at a median time of 2–3 h and eliminated with a mean terminal t 1/2 of 17.9–28.7 h with a dose range of 5–120 mg.…”
Section: Introductionmentioning
confidence: 99%
“…Although QT prolongation was observed after a single dose of 120 mg, DA-8031 was well tolerated after single doses of 80 mg or less. 16 …”
Section: Introductionmentioning
confidence: 99%
“…Dapoxetine has some minor "on demand" efficacy but clearly is not a breakthrough medicine in the treatment of PE [11]. Another SSRI, with a comparable profile as dapoxetine, DA-8031 is in development for PE, but efficacy data have not yet been elucidated [12,13]. Several other approaches for treatment of PE are used or are in development, including local anesthetics (e.g., lidocaine) used as cream, gel, or spray, and are moderately effective in delaying ejaculation [10].…”
mentioning
confidence: 99%